Peran Keterampilan Membaca dengan Strategi Membaca untuk Meningkatkan Prestasi: Meta-analisis - - Sudjiono; Wisjnu Martani (Buletin Psikologi, 2012)
The author tried to find out the corellation coefficient between reading skills and readingstrategi to achievement by quantitative meta-analysis. 65 studies were collected and analyzed. Theresults of the synthesis showed that the best estimate of the population correlation was 0.435(reading skills), 0.429 (reading strategy), and 0.434 ((reading skills and reading strategy) and thefrequency weighted average scuared error correlations corrected individually for artifacts about0.176. (reading skills), 0.0828 (reading strategy), and 0.154 (reading skills and reading strategy),with zero effect size standard deviation of all. Implications related to definition and instructionalcomponents that optimize the magnitude of outcomes are discussed.